PENGARUH IKLIM ORGANISASI, ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN ETOS KERJA TERHADAP KINERJA PEGAWAI (STUDI KASUS RSUD dr.H.L.M BAHARUDDIN, M.Kes Kab MUNA) - Tarsan, La Ode; Hakim, Adnan; Tangalayuk, Agustinus; Natsir, La Ode Abdul; Sinarwati, Sinarwati (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2023)
This study aims to (1) knowing influence organizational climate on employee performance staff at dr. H.L.M Baharuddin M.Kes, kab. Muna. (2) knowing the effect of organizational citizenship behavior (ocb) on the performance of employee at dr. H.L.M Baharuddin M.Kes, kab. Muna. (3) knowing the effect of work ethic on employee performance at dr. H.L.M Baharuddin M.Kes, kab. Muna. The objects in this study were nurses at dr. H.L.M Baharuddin M.Kes, Kab. Muna. However, the sampling method was purposive sampling using the slovin formula to obtain a sample of 71 nurses. Data collection methods in this study using questionnaires and documentation. Research data were analyzed using multiple linear regression through SPSS 25 Software. The results showed that (1) partially organizational climate has a significant positive effect on employee performance at dr. H.L.M Baharuddin M.Kes. (2) partially organizational citizenship behavior significant positive effect on employee performance at dr. H.L.M Baharuddin M.Kes. (3) partially work ethic significant positive effect on employee performance at dr. H.L.M Baharuddin M.Kes.